2011
DOI: 10.1186/1752-1947-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Unusual computed tomography findings of radionecrosis after chemoradiation of stage IV hypopharyngeal cancer: a case report

Abstract: IntroductionRadionecrosis (post-radiotherapy laryngeal submucosal inflammation and necrosis) is a complication of (chemo) radiotherapy for hypopharyngeal cancer that is difficult to differentiate from tumor recurrence.Case presentationA 67-year-old Japanese man presented with a condition extremely difficult to diagnose differentially as radionecrosis or tumor recurrence after radiotherapy for hypopharyngeal cancer. Although tumor recurrence was suspected from clinical conditions and computed tomography finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It has been shown by later research that radiotherapy may cause local tissue hypoxia, which can result in tissue fibrosis, endarteritis, vascular blockage, and decreased blood flow. The physiological function of the larynx is impacted, and the anatomical structure of the larynx is destroyed when microcracks in the perichondrium expose the deep surface cartilage to the air, resulting in infection and ultimately radionecrosis of cartilage ( 7 , 17 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by later research that radiotherapy may cause local tissue hypoxia, which can result in tissue fibrosis, endarteritis, vascular blockage, and decreased blood flow. The physiological function of the larynx is impacted, and the anatomical structure of the larynx is destroyed when microcracks in the perichondrium expose the deep surface cartilage to the air, resulting in infection and ultimately radionecrosis of cartilage ( 7 , 17 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microfissures of the perichondrium (both internal and external) appear, exposing the cartilage in its deep face to the bacteria of the aero-digestive tract. Infection sets in, leading to chondroradionecrosis, which is then considered a late complication 18,25,37 . The first report of larynx chondronecrosis due to radiotherapy was by Goodrich and Lenz, in 1948 38 , and since then not many cases have been reported, up to the present time a total of seventyseven patients, without including those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The tomographic findings of laryngeal changes during or shortly after radiotherapy are not able to rule out local recurrence. The findings are often nonspecific and the data in the literature are confusing, except for citing that the likelihood of relapse is greater within one year and that after this period the chance of chondroradionecrosis is higher 37,[39][40][41] . According to Hermans et al 40 , the local recurrence rate after radiotherapy is about 10% to 20% for T1 / T2 lesions and 40% to 50% for T3 / T4 lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Levin et al indicated that bevacizumab is a treatment option in patients who suffer from radiation necrosis secondary to treatment of head, neck and brain cancers [11]. We previously reported a case of a 67-year-old Japanese man who presented with a condition extremely difficult to diagnose differentially as radionecrosis or tumor recurrence after chemoradiotherapy for hypopharyngeal cancer [12]. Although tumor recurrence was suspected from clinical conditions and computed tomography findings, pathological analysis revealed no evidence of tumor recurrence, and successful therapy with steroids and antibiotics reduced the mucosa edema.…”
Section: The Role Of Bevacizumab In Treatment For Radiation Necrosis mentioning
confidence: 99%